L’exclusion des journalistes juifs des publications fascistes en Italie - Fanny Levin Gallina (Diasporas: Circulations, Migrations, Histoire, 2011)
The persecution of Jews in Italy is one of the most tragic aspects of fascist totalitarianism. In the wake of recent studies relating to the exclusion of intellectuals, this work intends to trace the history, barely studied, of journalists victims of racial laws. Within a few weeks, they were identified and struck off the professional list. Relegated to second class citizens, many were forced to seek the path of exile.